The Welfare Effects of Trump’s Tariff Policy - Todorova, Tamara (Theoretical and Practical Research in Economic Fields, 2025)
We discuss the terms-of-trade effects of the import tariffs imposed by the US administration. Import tariffs benefit a large nation by suppressing the export price of the good it imports and by improving its terms of trade. This allows the large nation to move to a higher consumption point without the need for actual economic growth. The terms-of-trade gain is substantive for a large nation, while there is none for a small open economy. Borrowing on international trade theory we argue that the purpose of the import tariffs imposed by the USA is not merely to resolve trade balance issues, but rather to effortlessly improve the consumption position of the country.